Two decades of axillary management in breast cancer. Issue 13 (12th November 2015) - Beek, M A; Verheuvel, N C; Luiten, E J T; Klompenhouwer, E G; Rutten, H J T; Roumen, R M H; Gobardhan, P D; Voogd, A C
Abstract: Background: Axillary lymph node dissection (ALND) in patients with breast cancer provides prognostic information. For many years, positive nodes were the most important indication for adjuvant systemic therapy. It was also believed that regional control could not be achieved without axillary clearance in a positive axilla. However, during the past 20 years the treatment and staging of the axilla has undergone many changes. This large population-based study was conducted in the south-east of the Netherlands to evaluate the changing patterns of care regarding the axilla, including the introduction of sentinel lymph node biopsy (SLNB) in the late 1990s, implementation of the results of the American College of Surgeons Oncology Group Z0011 study, and the initial effects of the European Organization for Research and Treatment of Cancer AMAROS study. Methods: Data from the population-based Eindhoven Cancer Registry of all women diagnosed with invasive breast cancer in the south of the Netherlands between January 1993 and July 2014 were used. Results: The proportion of 34 037 women staged by SLNB without completion ALND increased from 0 per cent in 1993–1994 to 69·0 per cent in 2013–2014. In the same period the proportion undergoing ALND decreased from 88·8 to 18·7 per cent. Among women with one to three positive lymph nodes, the proportion undergoing SLNB alone increased from 10·6 per cent in 2011–2012 to 37·6 per cent in 2013–2014. Conclusion: This population-based study demonstrated the radical transformation in management of the axilla since the introduction of SLNB and following the recent publication of trials on management of the axilla with a low metastatic burden. Abstract : Big changes